Comparative study of granulomatosis with polyangiitis subsets according to ANCA status: data from the French Vasculitis Study Group Registry. Issue 1 (16th March 2022) - Puéchal, Xavier; Iudici, Michele; Pagnoux, Christian; Cohen, Pascal; Hamidou, Mohamed; Aouba, Achille; Lifermann, François; Ruivard, Marc; Aumaître, Olivier; Bonnotte, Bernard; Maurier, Francois; Le Gallou, Thomas; et al.
Abstract : Objective: To investigate whether antineutrophil cytoplasm antibody (ANCA)-negative and myeloperoxidase (MPO)-ANCA–positive granulomatosis with polyangiitis (GPA) differ from proteinase-3 (PR3)-ANCA–positive GPA. Methods: Diagnostic characteristics and outcomes of newly diagnosed French Vasculitis Study Group Registry patients with ANCA-negative, MPO-ANCA–positive or PR3-ANCA–positive GPA satisfying American College of Rheumatology criteria and/or Chapel Hill Conference Consensus Nomenclature were compared. Results: Among 727 GPA, 62 (8.5%) were ANCA-negative, 119 (16.4%) MPO-ANCA–positive and 546 (75.1%) PR3-ANCA–positive. ANCA-negative patients had significantly (p<0.05) more limited disease (17.7% vs 5.8%) and less kidney involvement (35.5% vs 58.9%) than those PR3-ANCA–positive or MPO-ANCA–positive, with comparable relapse-free (RFS) and overall survival (OS). MPO-ANCA–positive versus PR3-ANCA–positive and ANCA-negative patients were significantly more often female (52.9% vs 42.1%), older (59.8 vs 51.9 years), with more frequent kidney involvement (65.5% vs 55.2%) and less arthralgias (34.5% vs 55.1%), purpura (8.4% vs 17.1%) or eye involvement (18.5% vs 28.4%); RFS was similar but OS was lower before age adjustment. PR3-positive patients' RFS was significantly lower than for ANCA-negative and MPO-positive groups combined, with OS higher before age adjustment. PR3-ANCA–positivity independently predicted relapse for all GPA forms combined but not when comparing only PR3-ANCA–positive versus MPO-ANCA–positive patients. Conclusions: Based on this large cohort, ANCA-negative versus ANCA-positive patients more frequently had limited disease but similar RFS and OS. MPO-ANCA–positive patients had similar RFS but lower OS due to their older age. PR3-ANCA–positive GPA patients' RFS was lower than those of the two other subsets combined but that difference did not persist when comparing only PR3 versus MPO-ANCA–positive patients.